ANALISIS IMPLEMENTASI PEMBIAYAAN AR-RAHN (GADAI SYARIAH) PADA KANTOR PEGADAIAN SYARIAH CABANG LANDUNGSARI MALANG - Afdhila, Galis Kurnia (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study obtain empirical evidence regarding sharia mortgage at Kantor Pegadaian Syariah cabang Landungsari Malang. Research method used is case study methode and explanatory type. This study describe the phenomenon of the research object, in this case is the Sharia mortgage financing at Kantor Pegadaian Syariah cabang Landungsari Malan compared with Fatwa DSN MUI as well as general accepted accounting standard. The data obtained through interview tehniques, participant observation, and documentation. Based on this research result, concluded that there are several aspects that must be adjust by the company with legal regulation. Those aspects are ujroh tarf still define based on loan as well as administrative cost and also incorporation of Rahn and Ijarah contract. In addition to this, Pegadaian Syariah Landungsari Malang has been implement sale of the collateral based on Fatwa DSN MUI. It seen by first contacting the customer when the loan has to paid, and refund the exces money from the sale. Key words : sharia mortgage (rahn), ujroh, administrative cost, incorporation contract, collateral (marhun)